Utilization Of Ayush Drugs In Pediatric Patients For Covid-19 And Associated Socio-Demographic Factors (Journal of Pharmaceutical Negative Results, 2023)
Background and objectives: COVID-19, is a contagious disease also known as severe acute respiratory syndrome corona virus 2 (SARS-CoV-2). All age groups among children are susceptible even though the severity of infection is less. Although the seropositivity rate was slightly lower as compared to adults, a significant percentage of children are seropositive for SARS‑CoV‑2. As of now, there is no definitive treatment for COVID-19 and management is largely supportive and empirical in modern medicine. For the prevention, treatment, and post-COVID management the role of AYUSH was of substantial importance. To combat the crisis, AYUSH was integrated in clinical practice and public health in the national efforts. Present study was carried out to evaluate the utilization of Ayush medications for COVID-19 among the pediatric patients who attended outpatient department (OPD) of the hospital.Methods: Present study was a cross-sectional observational study conducted from August 2021 to March 2022 among the pediatric patients aged 0-16 years. Convenience sampling which is a non-probability sampling technique was used. To record the results of the study a pre-tested semi structured questionnaire was used. Only those Unani, Ayurvedic and Homeopathic medicines that were recommended by ministry of Ayush and delivered through public health care system or were prescribed by a registered Ayush practitioner were considered as drugs for COVID-19 prophylaxis or treatment. Data was analyzed using Microsoft Excel  and SPSS software.Results: In this study we observed that overall, 31.53 % of the children aged 0 to 16 years of age have used Ayush medication during the period of COVID-19 pandemic for prevention and treatment of the infection. The utilization was higher in lower income groups and increased with the increase in the age of children.Conclusion: We conclude that better awareness about the availability of Ayush treatments for pediatric patients and scientific evidence about their efficacy and about their safety shall be prioritized.